Imaging of neuroinflammation in migraine with aura: A [11C]PBR28 PET/MRI study - Albrecht, D; Mainero, C; Ichijo, E; Ward, N; Granziera, C; Zürcher, N; Akeju, O; Bonnier, G; Price, J; Hooker, J; Napadow, V; Loggia, M; et al. (American Academy of Neurology, 2019)
Objective To determine if migraine with aura is associated with neuroinflammation, which has been suggested by preclinical models of cortical spreading depression (CSD) as well as imaging of human pain conditions. Methods Thirteen migraineurs with aura and 16 healthy controls received integrated PET/MRI brain scans with [11C]PBR28, a radioligand that binds to the 18 kDa translocator protein, a marker of glial activation. Standardized uptake value ratio (SUVR) was compared between groups, and regressed against clinical variables, using region of interest and whole-brain voxelwise analyses. Results Compared to healthy controls, migraineurs demonstrated SUVR elevations in nociceptive processing areas (e.g., thalamus and primary/secondary somatosensory and insular cortices) as well as in areas previously shown to be involved in CSD generation (visual cortex). SUVR levels in frontoinsular cortex, primary/secondary somatosensory cortices, and basal ganglia were correlated with frequency of migraine attacks. Conclusions These findings demonstrate that migraine with aura is associated with neuroimmune activation/neuroinflammation, and support a possible link between CSD and glial activation, previously observed in animals.